Study of novel parallel H-bridge and common-emitter current-source inverters for photovoltaic power conversion system - Suroso Suroso; Hari Siswantoro (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
A novel operation of three-level H-bridge and common-emitter current source inverters (CSIs) proposed for photovoltaic power converters is presented in this paper. Two photovoltaic systems with two different inverter circuits, i.e. H-bridge and common-emitter CSIs, were connected in parallel to supply a sharing ac power load. In order to regulate the power supplied by each inverter system, proportional integral current controllers were employed. Triangular carrier and sinusoidal signals-based modulation techniques were implemented to both inverters. Some parameters such as load current, inverter’s output current, total harmonics distortion (THD), and efficiency were tested and analyzed. Test results showed that in the parallel operation of these inverters, the average THD percentage of the load current was 0.34% for load power factor 0.996 and 0.62 % for load power factor 0.782. Minimum waveform distortion of inverter ac currents during parallel operation can be achieved if the current magnitudes of both inverters were set the same. In the case of efficiency, the maximum efficiency of the system was 89.07%. Operating the H-bridge CSI with a higher magnitude of the output current will result in higher efficiency of the system.